Comparative analysis of the antibody titers to different SARS-COV-2 vaccines in vaccinated tertiary students in Botswana - Maswabi, Bokang (My University, 2023)
Rapidly evolving new variants of SARS-CoV-2, e.g., alpha, beta, delta and omicron, were associated with higher transmissibility and pathogenicity causing new waves of infections in most countries. During the Covid-19 pandemic Botswana like most countries in Africa initiated a rigorous vaccine program to protect its population. Due to the dynamics of vaccine availability Botswana engaged in a heterologous mix and match vaccine strategy which relied on using generally available vaccines while. The country prioritised vulnerable citizens. Hence subjects received various vaccines and in various regimen in both Homologous and heterologous combinations. In Botswana, the administered vaccines included inactivated virus-based vaccines Sinovac/CoronaVac, mRNA-based vaccines Pfizer-BioNTech and Moderna and lastly viral vector-based vaccines AstraZeneca and Janssen by Johnson & Johnson. These vaccines stimulate immune responses, including B-cell (humoral/antibody) activation with subsequent production of antibodies (IgM, IgG, IgA) [2,3,4]. Research work was done to analyse and quantify induced antibody titers (IgM and IgG) in vaccinated and non-vaccinated individuals during the Covid-19 pandemic. We also enrolled participants in a longitudinal cohort-based sero-epidemiological survey to quantify the proportion of subjects who were seropositive at various points during Covid-19 pandemic.